Downward spectral solar radiance as measured in different depths under sea ice (transmitted radiance) at station PS122/4_45-129 on 2020-07-03 - Marcel Nicolaus; Philipp Anhaus; Stefanie Arndt; Christian Katlein; Daniela Krampe; Benjamin Allen Lange; Ilkka Matero; Julia Regnery; Jan Rohde; Martin Schiller (PANGAEA, 2022)
Downward spectral solar radiance as measured in different depths under sea ice (transmitted radiance). The radiance sensor (7° opening) was installed on the ROV.
In: Nicolaus, M et al. (2021): Spectral solar radiation over and under sea ice during the MOSAiC campaign 2019/20 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.935688